CROWNFUNDING SEBAGAI KONSTRUKSI SOSIAL TEKNOLOGI DAN MEDIA BARU - Wahyu Nurhadi; Irwansyah Irwansyah (Jurnal Komunikasi dan Kajian Media, 2018)
The presence of technology and new media does not come from empty space. Development of technology as a process of interaction or discourse between technologist and its relation with social group. Biker and Pinch in The Social Construction of Facts and Asrtefacts: or How the Sociology and the Sociology of Technology might Benefit Each Other (1984) say, the state of technology is like science, that is, as social construction, its course depends on many social factors and relationships between social groups. Crowdfunding as a new technology and media are present from social construction. Crowdfunding leverages technology by engaging the public to fundraising to help (donate) people in need and fundrasing for a project or business unit, which is done online, be it based on websites and applications. So as to enable the wider community to access (fundraising or become funders) charity programs or business projects. Crowdfunding such as Kitabisa.com site is one example of social construction technology (SCOT) which then move the positive trend of the world of philanthropy in IndonesiaKey Words: Social Construction, SCOT , crowdfunding, Kitabisa.com